Experimental evaluation of irradiation capsule design efficiency for molybdenum-99 production - D.S. Sairanbayev; M.T. Aitkulov; Sh.Kh. Gizatulin; A.N. Gurin; Ye.T. Chakrova; K.S. Kisselyov; A. Ch Ashibayev; A.A. Shaimerdenov (Nuclear Engineering and Technology, 2025)
Currently, technetium-99m is widely used in nuclear diagnostic medicine and is obtained from molybdenum-99. In Kazakhstan, the technology for producing 99Mo/99mTc generators to obtain a radiopharmaceutical was developed and introduced into serial production. Molybdenum-99 is produced via thermal neutron irradiation of molybdenum powder in a WWR-K reactor. However, in this case, the maximum specific activity generated is proportional to the cross-section of the radiation capture of a thermal neutron by the molybdenum-98 nucleus (0.13 b). In contrast, the epithermal neutron region offers higher cross-section resonances (6.9 b), suggesting potential for increased specific activity, which extends the generator operating time and improves its competitiveness. Based on this, an improved irradiation capsule design was developed to produce molybdenum-99 in a WWR-K reactor. The neutron characteristics of an irradiation capsule in the reactor core of a critical facility were also studied. This paper presents the results of experimental studies and demonstrates the effect of the irradiation capsule design on the energy distribution of neutrons. The possibility of increasing the specific activity of molybdenum-99 by 10 % when irradiating molybdenum with a natural isotopic composition and by 23 % when using molybdenum enriched to 98.6 % was demonstrated.